HISTOPATHOLOGICAL SPECTRUM AND ROLE OF CLINICOPATHOLOGICAL CORRELATION IN VESICULOBULLOUS LESIONS - A TERTIARY CARE HOSPITAL EXPERIENCE - Khursheed, Soffia; Shah, Hijab; Ijaz, Ammara; Mehmood, Muzna; Tanvir, Nida; Sharif, Shawana (Journal of Ayub Medical College Abbottabad, 2022)
Background: Histopathology is an important diagnostic modality for vesiculobullous lesions, however the diagnosis may at times require use of Immunofluorescence techniques which are expensive and not widely available. The aim of this study was to determine the histopathological spectrum of vesiculobullous diseases and to determine the role of clinic-pathological correlation in diagnosing bullous lesions. Methods: This was cross sectional validation study conducted in a tertiary care hospital, over a period of 18 months. All the clinically diagnosed cases of bullous diseases were included and examined as histological sections by three histopathologists. Results: Out of 58 total cases, the most frequently diagnosed lesions included Pemphigus vulgaris (27%), Bullous pemphigoid (13.8%) and Pemphigus foliaceous (12.1%). Females comprised 55% of cases, age distribution was wide but most patient were in age bracket of 20-39 years. Conclusion: There was 89.6% correlation between clinical and histopathological diagnosis. Only 2 cases were sent for Immunofluorescence studies, as histopathology was inconclusive in those cases. Therefore, we conclude that histopathological examination along with clinical correlation is a very useful way of diagnosing vesiculobullous disorders